Formin protein DAAM1 positively regulates PD-L1 expression via mediating the JAK1/STAT1 axis in pancreatic cancer - Rui Xu; Mengyun Wan; Jiadong Pan; Jie Mei; Ji Zhou; Yan Shen; Jiayue Yang; Yichao Zhu; Jing Sun (Cancer Cell International)
Abstract Background Dishevelled-associated activator of morphogenesis1 (DAAM1) is a member of the evolutionarily conserved Formin family and plays a significant role in the malignant progression of various human cancers. This study aims to explore the clinical and biological significance of DAAM1 in pancreatic cancer. Methods Multiple public datasets and an in-house cohort were utilized to assess the clinical relevance of DAAM1 in pancreatic cancer. The LinkedOmics platform was employed to perform enrichment analysis of DAAM1-associated molecular pathways in pancreatic cancer. Subsequently, a series of in vitro and in vivo experiments were conducted to evaluate the biological roles of DAAM1 in pancreatic cancer cells and its effects on intratumoral T cells. Results DAAM1 was found to be upregulated in pancreatic cancer tissues, with higher expression levels observed in tumor cells. Additionally, high expression of DAAM1 was associated with poor prognosis. DAAM1 acted as an oncogene in pancreatic cancer, and its inhibition suppressed tumor cell proliferation, migration, and invasion, while promoted apoptosis. Furthermore, DAAM1 was involved in the JAK1/STAT1 signaling pathway and regulated PD-L1 expression in pancreatic cancer cells. The inhibition of DAAM1 also significantly reduced the exhaustion levels of CD8+ T cells. Conclusion In conclusion, DAAM1 functions as an oncogene and is immunologically implicated in pancreatic cancer, these findings suggest that DAAM1 may serve as a promising therapeutic target for the clinical management of pancreatic cancer.